2023
DOI: 10.1002/dad2.12426
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride–glucose index, Alzheimer's disease plasma biomarkers, and dementia in older adults: The MIND‐China study

Abstract: Introduction Population‐based studies have rarely explored the associations of the triglyceride–glucose (TyG) index, a surrogate marker of insulin resistance, with dementia and plasma biomarkers for amyloid beta (Aβ) and neurodegeneration. Methods This population‐based study included 5199 participants (age ≥ 65 years); of these, plasma Aβ, total tau, and neurofilament light chain (NfL) were measured in 1287 persons. Dementia and subtypes were diagnosed following the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 47 publications
1
0
0
Order By: Relevance
“…Previous studies have found the correlation between triglyceride level and an increased risk of AD [17], in which high triglyceride level was significantly associated with an increased likelihood of dementia and AD. Among participants without cardiovascular disease or diabetes, the significant association with dementia remained and high triglyceride was associated with elevated plasma aβ [18]. Our study found that triglyceride was negatively correlated with Aβ1-40 and GFAP, which was consistent with previous research results to some extent.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have found the correlation between triglyceride level and an increased risk of AD [17], in which high triglyceride level was significantly associated with an increased likelihood of dementia and AD. Among participants without cardiovascular disease or diabetes, the significant association with dementia remained and high triglyceride was associated with elevated plasma aβ [18]. Our study found that triglyceride was negatively correlated with Aβ1-40 and GFAP, which was consistent with previous research results to some extent.…”
Section: Discussionsupporting
confidence: 92%